Nontraumatic hepatic hematoma caused by Wegener's granulomatosis: an unusual cause of abdominal pain - Doganay, Selim; Kocakoc, Ercan; Balaban, Mehtap (New Zealand Medical Assoc, 2010)
Wegener's granulomatosis (WG) is a vasculitis of unknown origin characterised by prominent involvement of upper and lower respiratory tract and kidney. There are only a handful of reported cases in the literature about hepatic involvement of WG. This report shows a patient with WG whose main complaint was severe abdominal pain due to nontraumatic subcapsular hepatic hematoma. To our knowledge, this is the first reported case of WG with hepatic hematoma depicted by US and CT in the English literature.